Assessment of Bleeding Severity and Prevalence of Iron Deficiency Among Hemophilia B Carriers By Factor IX Activity Levels - Lu, Zhexi; Machin, Nicoletta C (Blood, 2024)
Background Hemophilia B, traditionally thought to only impact men due to its X-linked recessive inheritance, also affects a subset of women who exhibit increased bleeding tendencies. These women demonstrate a wide range of factor IX activity levels, which poorly correlate with bleeding severity; even mildly reduced clotting factor levels (0.41-0.60 IU/mL) are associated with bleeding events. Studies indicate that women with hemophilia B and symptomatic carriers may experience spontaneous hemorrhages and heightened bleeding during surgeries and trauma. Additionally, women with hemophilia frequently encounter heavy menstrual bleeding and an elevated risk of postpartum hemorrhage. Prolonged blood loss predisposes these individuals to iron deficiency and anemia. Timely identification and management of iron deficiency is crucial for improving physical and mental health and enhancing health-related quality of life. We hypothesize that factor IX levels would show a weak relationship between bleeding severity and the degree of iron deficiency among hemophilia B carriers. Aim To evaluate the relationship between factor IX activity levels, bleeding scores, and the prevalence of iron deficiency in hemophilia B carriers. Methods We conducted a retrospective record review of hemophilia B carriers seen at the Hemophilia Center of Western Pennsylvania between 2015-2023. Confirmed carriers ≥ 10 years old were included to capture heavy menstrual bleeding. Data on demographics, clotting factor levels, and lowest ferritin values were extracted from electronic health records. Bleeding severity was quantified using the ISTH-BAT based on clinical documentation. Descriptive statistics were performed, and linear regression was used to compare continuous variables, with a significance level set at p < 0.05. Statistical analyses were performed using Stata 17.0. Results: 129 hemophilia B carriers aged 10-74 years (mean age 31.3, SD 14.2) were identified. Of whom 89 (69%) patients were Amish, sharing the same familial F9c.1025T>C p.Thr34Met mutation. The average factor IX activity level was 0.56 IU/mL (SD 0.21 IU/mL). Among these, 103 (79.8%) had factor IX activity levels ≥0.40 IU/mL, 24 (18.6%) had mild hemophilia, and 2 (0.02%) had moderate hemophilia. No severe cases were found. Bleeding scores were available for 75 (58.1%), with an average score of 4.81 (SD 3.5). Ferritin results were available for 57 (44.2%), with a mean of 29.1 ng/mL (SD 39.2 ng/mL); 93% (53/57) had ferritin results < 50 ng/mL. Regression analysis of 56 subjects showed that factor IX activity significantly predicts bleeding scores (F(1,54)=10.28, p=0.002, R2=0.16). Each unit increase in factor IX activity decreased the bleeding score by 6.67 points (β=−6.67, p=0.002, 95% CI: -10.83 to -2.50). The model's root mean squared error was 3.34. Including age in the model did not significantly impact results, with factor IX activity and age together explaining 30.9% of the variability, suggesting other contributing factors. Conclusion: Our study revealed that while higher factor IX activity is associated with fewer bleeding symptoms, there is significant variability in bleeding scores not fully explained by factor IX activity or age, indicating other contributing factors. This variability exists even among a fairly homogeneous group of primarily Amish patients (69%) with the familial F9c.1025T>C p.Thr34Met mutation. Given that factor IX activity is not a robust predictor of bleeding severity, clinical bleeding assessment is crucial for all patients. The high prevalence of iron deficiency (93% with ferritin < 50 ng/mL) underscores the importance of routine ferritin screening and early intervention, regardless of factor activity levels. These findings highlight the need for further research to identify additional factors influencing bleeding phenotypes in women and carriers with hemophilia B. Machin:Takeda: Research Funding; Sanofi: Honoraria.